Disseminated hydatid disease, both above and below diaphragm: a rare presentation - Singla, Neeraj; Agrawal, Suraj (International Journal of Advances in Medicine, 2021)
Echinococcosis is a common infectious disease in middle east countries. Human being, sheep, swine and goat are in determinate accidental hosts while dog is definitive host. Liver is most common site of involvement but simultaneous affection of another organ may occur in abdominal cavity. We present a case of hydatid disease with liver, spleen and lung involvement simultaneously which is a rare presentation.